Detection of a new community genotype methicillin-resistant staphylococcus aureus clone that Is unrelated to the USA300 clone and that causes pediatric infections in Colombia (2013)
The dissemination of a clone of community genotype methicillin-resistant Staphylococcus aureus (CG-MRSA) that is related to USA300 has been reported in Latin America. We recently detected isolates of a new clone of CG-MRSA (spa type t1635 and ACME-negative) that was genetically unrelated to the USA300 clone and that causes infections in children in Colombia. This finding indicates the appearance of a new clone of CG-MRSA in our region.